Pengembangan Bahan Ajar Tematik Berbasis Budaya Lokal untuk Siswa Kelas IV Sekolah Dasar - Stefanus Divan (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: Based on requirement analysis in Grade IV SDI Bangkakeli Manggarai found the problem happened, teaching materials used by teachers still using KTSP 2006 teaching materials, teachers tend to use teaching materials developed by publishers and not in accordance with the characteristics and cultural environment of students. The solution of the problem is to develop the local culture-based thematic materials in accordance with the culture and environment of the students. The development of thematic materials using the model of Dick and Carey (2009). The steps of this development model are done up to step 9, ie revising the learning materials. Step 10 is eliminated because in this study only prototype product obtained only, in accordance with the purpose of research and development. Based on the results of these trials, these thematic materials are very valid, very interesting, effective and applicable in learning. It can be known from the validation test result from the material experts by 93.84% of the design experts by 94.19% and the linguist by 67.14%. The attractiveness of the product with an average score of 90.41% is included in the criteria is very interesting. Effective products are used with an average of 90% entering in very effective criteria. And product availability is very attractive with an average of 93.00%. Abstrak: Berdasarkan analisis kebutuhan di Kelas IV SDI Bangkakeli Manggarai ditemukan permasalahan yang terjadi, bahan ajar yang digunakan oleh guru masih menggunakan bahan ajar KTSP 2006, guru cenderung menggunakan bahan ajar yang dikembangkan oleh penerbit dan tidak sesuai dengan karakteristik dan lingkungan budaya siswa. Pemecahan masalah yang dilakukan adalah dengan mengembangkan bahan ajar tematik berbasis budaya lokal yang sesuai dengan budaya dan lingkungan siswa berada. Pengembangan bahan ajar tematik ini menggunakan model Dick dan Carey (2009). Langkah-langkah model pengembangan ini dilakukan sampai pada langkah ke 9, yaitu merevisi bahan pembelajaran. Langkah 10 ditiadakan karena dalam penelitian ini hanya diperoleh prototipe produk saja, sesuai dengan tujuan penelitian dan pengembangan. Berdasarkan hasil uji coba tersebut, bahan ajar tematik ini sangat valid, sangat menarik, efektif dan dapat diterapkan dalam pembelajaran. Hal ini dapat diketahui dari hasil uji validasi dari ahli materi sebesar 93,84% ahli desain sebesar 94,19% dan ahli bahasa sebesar 67,14%. Tingkat kemenarikan produk dengan skor rata-rata sebesar 90,41% masuk dalam kriteria sangat menarik. Produk efektif digunakan dengan rata-rata sebesar 90% masuk dalam kriteria sangat efektif. Dan keterterapan produk sangat menarik dengan rata-rata sebesar 93,00%.